Biosynthesis, Characterization, and Antifungal Activity of Copper Oxide Nanoparticles Using Myrtaceae Plant Extracts - Vrushali Ghodke,; Anil Athare,; Sushama Takate, (International Journal of Scientific Research in Science and Technology, 2026)
Copper oxide nanoparticles (CuO NPs) were biogenically synthesized using aqueous extracts from Psidium guajava, Syzygium cumini, and Syzygium aromaticum, which are all members of the Myrtaceae family. Characterization was performed utilizing UV-Vis, FTIR, XRD, and SEM-EDS, confirming the synthesis of nanoparticles. The CuO nanoparticles exhibited significant antifungal activity against Candida albicans using the agar well diffusion method. The extract of Syzygium aromaticum-mediated nanoparticles demonstrated the highest bioactivity.
Keywords: Green synthesis; CuO nanoparticles; Myrtaceae; Candida albicans